A comparison of the Qumran community and Hare Krishna movement regarding motivations for separation from mainstream religion as cults of purity and holiness : research article - Dennill, G. B. (Journal for semitics, 2008)
This paper provides a comparison of the theological bases for the separation of the Qumran community and the Hare Krishna movement from mainstream religion as cults of purity and holiness. This concerns the leadership of divine, authoritative spiritual masters and initiation rites, moral impurity and the punishment of moral offences because these maintain the boundaries of a schismatic sect. Comparisons of specific theological issues are given under separate headings; the positions of the Hare Krishna movement are directly compared with those of the Qumran community as reflected in the scrolls.